The Transcriptional Cofactor VGLL1 Drives Transcription of Human Papillomavirus Early Genes via TEAD1 - Mori, Seiichiro (J Virol, 2020)
The TEAD family of transcription factors requires associating cofactors to induce gene expression. TEAD1 is known to activate the early promoter of human papillomavirus (HPV), but the precise mechanisms of TEAD1-mediated transactivation of the HPV promoter, including its relevant cofactors, remain unexplored. Here, we reveal that VGLL1, a TEAD-interacting cofactor, contributes to HPV early gene expression. Knockdown of VGLL1 and/or TEAD1 led to a decrease in viral early gene expression in human cervical keratinocytes and cervical cancer cell lines. We identified 11 TEAD1 target sites in the HPV16 long control region (LCR) by in vitro DNA pulldown assays; 8 of these sites contributed to the transcriptional activation of the early promoter in luciferase reporter assays. VGLL1 bound to the HPV16 LCR via its interaction with TEAD1 both in vitro and in vivo. Furthermore, introducing HPV16 and HPV18 whole genomes into primary human keratinocytes led to increased levels of VGLL1, due in part to the upregulation of TEADs. These results suggest that multiple VGLL1/TEAD1 complexes are recruited to the LCR to support the efficient transcription of HPV early genes. IMPORTANCE Although a number of transcription factors have been reported to be involved in HPV gene expression, little is known about the cofactors that support HPV transcription. In this study, we demonstrate that the transcriptional cofactor VGLL1 plays a prominent role in HPV early gene expression, dependent on its association with the transcription factor TEAD1. Whereas TEAD1 is ubiquitously expressed in a variety of tissues, VGLL1 displays tissue-specific expression and is implicated in the development and differentiation of epithelial lineage tissues, where HPV gene expression occurs. Our results suggest that VGLL1 may contribute to the epithelial specificity of HPV gene expression, providing new insights into the mechanisms that regulate HPV infection. Further, VGLL1 is also critical for the growth of cervical cancer cells and may represent a novel therapeutic target for HPV-associated cancers.